Case Report: A 62-Year-Old Woman With Contrast-Induced Encephalopathy Caused by Embolization of Intracranial Aneurysm - Zhang, Ying; Zhou, Ming; Wang, Dong; Liu, Tao; Chang, Pengfei; Zhang, Jie; Zhang, Rui; Luo, Yumin; Liu, Ping (Frontiers in Surgery, 2021)
Contrast-induced encephalopathy (CIE) is a rare complication of endovascular treatment and is extensively reported as a transient and reversible phenomenon. This report describes a 62-year-old woman for embolization of an internal carotid artery (ICA) aneurysm. The operation was successful, but postoperation the patient suffered unconsciousness, blindness, hemiplegia, ophthalmoplegia, fever, and seizures. CT of the brain without the contrast showed widespread edema in the right cerebral hemisphere, which is involved in the frontal, parietal, temporal, and occipital lobes. She was diagnosed with CIE in time and treated with supportive management as soon as possible, and fortunately, the patient improved a benign course and was discharged without any neurological deficits. This study emphasizes the prevention of the CIE and the importance of early diagnosis and symptomatic treatment.